Associations of MRI‐Derived Glymphatic System Impairment With Global White Matter Damage and Cognitive Impairment in Mild Traumatic Brain Injury: A DTI‐ALPS Study - Yang, Dian‐Xu; Sun, Zheng; Yu, Meng‐Meng; Zou, Qiao‐Qiao; Li, Peng‐Yang; Zhang, Jing‐Kun; Wu, Xue; Li, Yue‐Hua; Wang, Ming‐Liang (Journal of magnetic resonance imaging, 2024)
Background Assessing the glymphatic function using diffusion tensor image analysis along the perivascular space (DTI‐ALPS) may be helpful for mild traumatic brain injury (mTBI) management. Purpose To assess glymphatic function using DTI‐ALPS and its associations with global white matter damage and cognitive impairment in mTBI. Study Type Prospective. Population Thirty‐four controls (44.1% female, mean age 49.2 years) and 58 mTBI subjects (43.1% female, mean age 48.7 years), including uncomplicated mTBI (N = 32) and complicated mTBI (N = 26). Field Strength/Sequence 3‐T, single‐shot echo‐planar imaging sequence. Assessment Magnetic resonance imaging (MRI) was done within 1 month since injury. DTI‐ALPS was performed to assess glymphatic function, and peak width of skeletonized mean diffusivity (PSMD) was used to assess global white matter damage. Cognitive tests included Auditory Verbal Learning Test and Digit Span Test (forward and backward). Statistical Tests Neuroimaging findings comparisons were done between mTBI and control groups. Partial correlation and multivariable linear regression assessed the associations between DTI‐ALPS, PSMD, and cognitive impairment. Mediation effects of PSMD on the relationship between DTI‐ALPS and cognitive impairment were explored. P‐value <0.05 was considered statistically significant, except for cognitive correlational analyses with a Bonferroni‐corrected P‐value set at 0.05/3 ≈ 0.017. Results mTBI showed lower DTI‐ALPS and higher PSMD, especially in complicated mTBI. DTI‐ALPS was significantly correlated with verbal memory (r = 0.566), attention abilities (r = 0.792), executive function (r = 0.618), and PSMD (r = −0.533). DTI‐ALPS was associated with verbal memory (β = 8.77, 95% confidence interval [CI] 5.00, 12.54), attention abilities (β = 5.67, 95% CI 4.56, 6.97), executive function (β = 2.34, 95% CI 1.49, 3.20), and PSMD (β = −0.79, 95% CI −1.15, −0.43). PSMD mediated 46.29%, 20.46%, and 24.36% of the effects for the relationship between DTI‐ALPS and verbal memory, attention abilities, and executive function. Data Conclusion Glymphatic function may be impaired in mTBI reflected by DTI‐ALPS. Glymphatic dysfunction may cause cognitive impairment related to global white matter damage after mTBI. Level of Evidence 2 Technical Efficacy Stage 2